Economic potential of PV for Italian residential end-users. (1st June 2020) - Lazzeroni, Paolo; Moretti, Francesco; Stirano, Federico
Abstract: The installation of PV systems in the Italian residential sector represents the main component within the overall PV market. Nevertheless, a strong contraction of PV investment can be observed in Italy during the last period due to the closure of the feed-in-tariff mechanism. For this reason, new opportunities have been introduced by the Italian Government to support investment in the residential sector: net-metering, tax deduction and a novel regulatory scheme where PV production can be exchanged between an end-user and an energy-provider free of network charges. In this context, an economic assessment for PV installations in residential households is presented in this paper considering the benefits derived by the combination of these supporting schemes presently available in Italy. Increasing electricity consumptions of residential end-user are considered to explore the feasibility of PV installation in different configurations. Geographical information system is used here as a supporting tool to take into account the variation of solar radiation resource across the country, since economic results are influenced by the match between energy consumption and PV production. The results highlight how the perspective of PV investment is still positive even if a feed-in-tariff for PV production is no longer available. Highlights: Economic potential of PV for Italian households with different electricity demand. Energy modeling considering solar radiation variability through GIS tool. The results highlight how the perspective of PV investment is still positive. The new regulatory framework can contribute to improve PV diffusion.